2011
DOI: 10.3233/jad-2011-110794
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the Tau Kinases Pathway May Modify the Risk and Age at Onset of Alzheimer's Disease

Abstract: Tau abnormal hyperphosphorylation and the formation of neurofibrillary tangles in the Alzheimer's disease (AD) brain is the result of upregulation of tau kinases. In a group of 729 Spanish late-onset AD patients and 670 healthy controls, we examined variations into a set of 20 candidate genes of kinases involved in tau phosphorylation at AD-related sites (PRKACB; CAMK2A; MARK1, 2, 3 and 4; CSNK1D; CDC2; RPS6KB1 and 2; p38α and β; IB1; JNK1, 2 and 3; MEK1 and 2; ERK1 and 2), to address hypotheses of genetic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…To identify the mammalian homologs of C55B7.10 and cdc‐7 , we employed an National Center for Biotechnology Information (NCBI) Basic Local Alignment Search Tool (BLAST) search to compare the C. elegans kinase domain protein sequences against the database of human proteins, and the reciprocal BLAST results comparing the human protein kinase domain against the database of C. elegans proteins (Supplementary Table 2). C55B7.10 has identity to the tau tubulin kinases TTBK1 and TTBK2, which are implicated in the pathological phosphorylation of tau in animal models, Alzheimer's disease, and SCA11 (see Table). cdc‐ 7 is the only C. elegans homolog of CDC7, which has multiple roles, including promoting initiation and maintenance of DNA replication, chromosome segregation during meiosis and mitosis, and DNA damage checkpoint response (see Table).…”
Section: Resultsmentioning
confidence: 99%
“…To identify the mammalian homologs of C55B7.10 and cdc‐7 , we employed an National Center for Biotechnology Information (NCBI) Basic Local Alignment Search Tool (BLAST) search to compare the C. elegans kinase domain protein sequences against the database of human proteins, and the reciprocal BLAST results comparing the human protein kinase domain against the database of C. elegans proteins (Supplementary Table 2). C55B7.10 has identity to the tau tubulin kinases TTBK1 and TTBK2, which are implicated in the pathological phosphorylation of tau in animal models, Alzheimer's disease, and SCA11 (see Table). cdc‐ 7 is the only C. elegans homolog of CDC7, which has multiple roles, including promoting initiation and maintenance of DNA replication, chromosome segregation during meiosis and mitosis, and DNA damage checkpoint response (see Table).…”
Section: Resultsmentioning
confidence: 99%
“…Vazquez-Higuera et al investigated genetic variations in a set of 20 candidates kinases involved in tau phosphorylation at sites correlating with AD (53). They reported that the distribution of the minor allele frequencies for these kinases did not differ significantly between sufferers and control groups, except for S6K2 where variations in intron 2 was increased in patients (50%) versus controls (39%).…”
Section: Tissue Expression Of S6k2 In Health and Diseasementioning
confidence: 99%
“…According to previous study, there are six isoforms of tau in human central nervous system (CNS) ringing in size from 352 to 441 amino acids, which generated by alternative splicing (Hanger et al, 2009). Many kinases have been proved to be tau kinases in earlier investigations (Vázquez-Higuera et al, 2011; Martin et al, 2013). To identify the targets of these tau kinases, large-scale studies aimed at determining phosphosites were done, and produced much information as reference.…”
Section: Resultsmentioning
confidence: 97%
“…Dual phosphorylation of MAPK1 at T183 and Y185 could be necessary for the activation of MAPK1 (Robbins et al, 1993) and we found slightly increase in the phosphorylation level of MAPK1 at these two sites induced by GFKP-19 treatment (Table S1). MAPK14 (p38α) had been reported to be a potential kinase of tau, and was related to a later onset of AD (Vázquez-Higuera et al, 2011). Phosphorylation of MAPK14 at T180 is necessary for its activation, while phosphorylation at both T180 and Y182 was more active than phosphorylation at T180 only (Zhang et al, 2008).…”
Section: Resultsmentioning
confidence: 99%